(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current state of pharmaceutical management at the Tan Phu District Health Center, Dong Nai Province, in 2024-2025. Method: Study design: cross-sectional descriptive study, surveying drug warehouse operations at the Tan Phu District Health Center based on 08 criteria from GSP (Good Storage Practice) in Annex IV of Circular No. 36/2018/TT-BYT Results: The criteria for personnel, facilities and equipment, drug storage, and self-inspection were found to be non-compliant with GSP standards. The criteria for receiving goods, distribution, records and documentation, and returned or recalled drugs met the GSP standards Conclusion: Appropriate solutions should be implemented for the criteria that do not meet GSP standards to enhance pharmaceutical management at the Tan Phu District Health Center in the upcoming period.